How are you creative ? : Innowiz kaarten. - Industrial Design Center (Kortrijk : Howest University - Ghent University Association, 2012)
A design thinking iteration in 4 steps. A set of 50 inspiring cards with creativity techniques, supporting these 4 steps. Numerous ways of combining the cards into your own personal development process.
Bevat: 50 inspiring cards